Jak wspierać rozwój innowacji społecznych? - Kwaśnicki, Witold (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The fundamental question that attempts to be answered in this article is following: To what extend supporting and subsidizing of the development of social economy and social innovation by the European Union and European governments is needed and justified?
Keywords: innowacje społeczne; ekonomia społeczna; rząd; dotacje rządowe